Legal but environmentally harmful practices involved in gold mining in Madre de Dios, Peru - Espín M., Johanna (Critical criminology, 2023)
The aim of this research is to examine environmental harms produced by artisanal and small-scale gold mining (ASGM) in the region of Madre de Dios, Peru. This study evaluates explanations for legal but environmentally harmful practices involved in ASGM from a sociological institutionalist approach, which offers a theoretical lens for considering various political, social, and administrative explanations. Data are drawn from the Peruvian legal framework relevant to ASGM, field observation, and key informants from different sectors. The findings provide greater clarity as to the extent those specific institutional explanations, such as regulatory capture and red tape, would account for lawful but awful environmental harms produced by ASGM.